Factores organizacionales y su influencia en la rotación de personal administrativo en la empresa Inversiones Promutel SAC, agencia Trujillo, año 2016 - Paz Temoche, Jennifer Natalí (2017)
The present work was prepared with the purpose of determining the level of influence of the organizational factors in the staff turnover of the company “Inversiones Promutel SAC.”, agency Trujillo, Year 2016. With the accomplishment of the present research work , I´d obtained information that help to identify the organizational factors that influence the personnel rotation, allowing other companies to take correctional policies to fight it and in this way to achieve that the workers will have a better labor stability. The design was used “transeccional correlacional no causal, and there were applied surveys to the workers and an interview to the Manager as a technique of investigation. As result of this investigation , was that the organizational factors have a high influence in the staff turnover of the company “Inversiones Promutel Sac.”, because it was found that the unsuitable management of these, did that the index of rotation of the period in study was high; in that way , the workers consider to be priority to have opportunities of professional growth, which recognize its achievements , also to be in positions according to its profile.